2020
DOI: 10.3390/catal10101210
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Intermolecular Alkyne Hydrofunctionalizations—Mechanistic Insights

Abstract: An overview of the current state of mechanistic understanding of gold-catalyzed intermolecular alkyne hydrofunctionalization reactions is presented. Moving from the analysis of the main features of the by-now-generally accepted reaction mechanism, studies and evidences pointing out the mechanistic peculiarities of these reactions using different nucleophiles HNu that add to the alkyne triple bond are presented and discussed. The effects of the nature of the employed alkyne substrate and of the gold catalyst (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 133 publications
0
26
0
Order By: Relevance
“…While palladium has historically dominated this field, other transition metals have arisen as efficient and orthogonal alternatives. Gold has been typically exploited in catalysis mostly for its Lewis acidity, [27] however, a number of studies have demonstrated the involvement of its redox chemistry in several cross‐coupling reactions using external oxidants, photoredox catalytic cycles or chelating/hemilabile ligands. [ 2c , 2d , 4f , 28 ] Further developments in this still young area of gold‐promoted cross‐coupling reactions have been hampered by the scarce mechanistic understanding of the individual steps along the proposed catalytic cycles.…”
Section: Discussionmentioning
confidence: 99%
“…While palladium has historically dominated this field, other transition metals have arisen as efficient and orthogonal alternatives. Gold has been typically exploited in catalysis mostly for its Lewis acidity, [27] however, a number of studies have demonstrated the involvement of its redox chemistry in several cross‐coupling reactions using external oxidants, photoredox catalytic cycles or chelating/hemilabile ligands. [ 2c , 2d , 4f , 28 ] Further developments in this still young area of gold‐promoted cross‐coupling reactions have been hampered by the scarce mechanistic understanding of the individual steps along the proposed catalytic cycles.…”
Section: Discussionmentioning
confidence: 99%
“…DFT studies vigorously promoted the investigations of mechanism for Au(I)‐catalyzed hydroamination [59–62] and gave the general information of intermediate bonding, N‐nucleophile types in the dehydrogenation step and the energetics of the whole catalytic cycle. Based on the mechanism of gold(I) catalyzed hydroamination, [63–66] the triangular tri‐gold species were proposed to firstly interact with an terminal alkyne and form a catalytically active cationic Au(I)‐alkyne complex in situ. For gold catalyzed functionalization of terminal alkynes like hydroamination or hydrophenoxylation, di‐gold σ, π‐acetylide complexes are more and more considered as the activated intermediates due to their easy access and properties [67–77] .…”
Section: Resultsmentioning
confidence: 99%
“…With the help of known information on the hydroalkoxylation reaction, numerous research groups have focused their efforts on the intermolecular hydrophenoxylation of (13) Gold catalysts bearing N-heterocyclic carbene (NHC) ligands are currently being studied due to their high catalytic activity in the alkyne hydroalkoxylation field [32]. However, gold catalysts containing NHC ligands in the presence of alkyne compounds can form π-complexes with an electrophilic character [33] and are capable to carry out a nucleophilic attack by nucleophiles such as alcohols or amines to obtain vinyl amines or ethers [34]. In addition, current reports have revealed that the steric demand from NHC ligands and the solvent effect play a significant role in gold-mediated catalysis.…”
Section: Hydroalkoxylationmentioning
confidence: 99%